The incidence of Attention Deficit Hyperactivity Disorder and related factors in a sample of Afrikaans-speaking Sub A (Grade 1) pupils - Brauer, Hans Georg (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1991.